The Prevalence of ADHD in American Society: The Influence of Parent-Child and Child-Technology Interactions - Steve, Amy; Grubb, Henry J. (European Scientific Journal, ESJ, 2018)
Attention Deficit Hyperactivity Disorder (ADHD) is a behavioral disorder that begins in childhood and persists throughout adulthood and is characterized by symptoms of inattention, hyperactivity, and impulsivity. Societal attitudes classify the diagnosis of ADHD differently in establishing what behaviors are deemed acceptable or tolerable in children depending on the particular region or area. American culture provides an important framework for societal perspectives of how ADHD is expressed through behaviors that are considered an abnormal pathology. The purpose of this study is to conduct a literature review of ADHD in various cultures to ascertain why the prevalence of this disorder continues to rise in American society. The hypothesis we assume for the increased rates of ADHD in our society is based on a linkage of events created by effects from a lack of parent-child interactions that lead to an increase in technology use which develops behaviors that mimic ADHD-like traits.